Effects of hydrological regime and land use on in-stream Escherichia coli concentration in the Mekong basin, Lao PDR - Nakhle, Paty; Ribolzi, Olivier; Boithias, Laurie; Rattanavong, Sayaphet; Auda, Yves; Sayavong, Saysongkham; Zimmermann, Rosalie; Soulileuth, Bounsamay; Pando, Anne; Thammahacksa, Chanthamousone; Rochelle-Newall, Emma J.; Santini, William; et al. (Scientific reports, 2021)
In the basin of Mekong, over 70 million people rely on unimproved surface water for their domestic requirements. Surface water is often contaminated with fecal matter and yet little information exists on the underlying mechanisms of fecal contamination in tropical conditions at large watershed scales. Our objectives were to (1) investigate the seasonality of fecal contamination using Escherichia coli as fecal indicator bacteria (FIB), and (2) establish links between the fecal contamination in stream water and its controlling factors (hydrology and land use). We present the results of (1) a sampling campaign at the outlet of 19 catchments across Lao PDR, in both the dry and the rainy seasons of 2016, and (2) a 10-day interval monitoring conducted in 2017 and 2018 at three point locations of three rivers (Nam Ou, Nam Suang, and Mekong) in northern Lao PDR. Our results show the presence of fecal contamination at most of the sampled sites, with a seasonality characterized by higher and extreme E. coli concentrations occurring during the rainy season. The highest E. coli concentrations, strongly correlated with total suspended sediment concentrations, were measured in catchments dominated by unstocked forest areas, especially in mountainous northern Lao PDR and in Vientiane province.